Answer:multiple
Step-by-step explanation:
Research
are produced.
Answer: 60%
Step-by-step explanation:
Given: The number of games lost by the soccer team last year =5
The number of games lost by the soccer team this year= 2
The decrease in losses=
The percent decrease in losses is given by :-
Hence, the percent decrease in losses is 60%.
energy is always transformed from one form to another
energy is not created nor destroyed
so when a car starts moving the chemical potential energy of the car is converted to kinetic energy
kinetic energy is the energy that moving objects possess
kinetic energy formula is as follows
Kinetic energy = 1/2 mv²
where m - mass
v - velocity
substituting these values
K.E = 1/2 x 1350 kg x (12 m/s)²
= 1/2 x 1350 x 144 = 97200 J
the kinetic energy of the car is 97.2 kJ
Hello!
A 1350 kg car travels at 12 m/s. What is it's kinetic energy ?
We have the following data:
m (mass) = 1350 kg
v (velocity) = 12 m/s
KE (kinetic Energy) = ? (in Joule)
Formula to calculate kinetic energy:
Solving:
_______________________
Answer: he has 5 groups and 2 remainders
Step-by-step explanation:
17÷ 3= 5 that will be 15
17-15= 2
Answer:
5 groups, 2 remaining
Step-by-step explanation:
17/3=5...2
Answer:
29-(2c+3)=2(c+3)+c=
We move all terms to the left:
29-(2c+3)-(2(c+3)+c)=0
We get rid of parentheses
-2c-(2(c+3)+c)-3+29=0
Step-by-step explanation:
Answer:
Solution for 29-(2c+3)=2(c+3)+c equation:
Simplifying
29 + -1(2c + 3) = 2(c + 3) + c
Reorder the terms:
29 + -1(3 + 2c) = 2(c + 3) + c
29 + (3 * -1 + 2c * -1) = 2(c + 3) + c
29 + (-3 + -2c) = 2(c + 3) + c
Combine like terms: 29 + -3 = 26
26 + -2c = 2(c + 3) + c
Reorder the terms:
26 + -2c = 2(3 + c) + c
26 + -2c = (3 * 2 + c * 2) + c
26 + -2c = (6 + 2c) + c
Combine like terms: 2c + c = 3c
26 + -2c = 6 + 3c
Solving
26 + -2c = 6 + 3c
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '-3c' to each side of the equation.
26 + -2c + -3c = 6 + 3c + -3c
Combine like terms: -2c + -3c = -5c
26 + -5c = 6 + 3c + -3c
Combine like terms: 3c + -3c = 0
26 + -5c = 6 + 0
26 + -5c = 6
Add '-26' to each side of the equation.
26 + -26 + -5c = 6 + -26
Combine like terms: 26 + -26 = 0
0 + -5c = 6 + -26
-5c = 6 + -26
Combine like terms: 6 + -26 = -20
-5c = -20
Divide each side by '-5'.
c = 4
Simplifying
c = 4
The measure of the angle ∠C to two decimal places will be 117.99°.
The squared of the size of any solitary side of either a triangle is equal, by the cosine rule, to the total of the squares of the lengths of the other two sides, times by the cosine of something like the angle they are a part of.
Let the triangle ΔABC, then the cosine law is given as,
c² = a² + b² - 2 a·b cos C
In ΔABC, if the length of sides a, b, and c are 3.5 centimeters, 5.5 centimeters, and 6 centimeters respectively. Then the measure of the angle ∠C is given as,
6² = (3.5)² + (3.5)² - 2 · (3.5) · (3.5) cos C
Simplify the equation, then we have
6² = (3.5)² + (3.5)² - 2 · (3.5) · (3.5) cos C
36 = 12.25 + 12.25 - 24.50 cos C
11.5 = - 24.50 cos C
cos C = - 11.5 / 24.5
C = 117.99
The measure of the angle ∠C to two decimal places will be 117.99°.
More about the cosine law link is given below.
#SPJ6